NECESIDAD DE LA DESIGNACIÓN DE UN DEFENSOR PÚBLICO EN PROCESOS EN LOS QUE SE RESUELVAN ASUNTOS DE NIÑOS Y ADOLESCENTES DE PATRIA POTESTAD - Reyes Encalada, Rosa Irene (2019)
This thesis entitled: "NEED FOR THE DESIGNATION OF A PUBLIC DEFENDER IN PROCESSES IN WHICH MATTERS OF CHILDREN AND ADOLESCENTS OF PATRIA POTESTAD ARE RESOLVED", the interest to develop arises when analyzing the legal regulations of protection of minors in trials of family as the conflict of parental rights that the possession and visiting regime is aired, children and adolescents being represented by their parents or relatives as tutors, or curators; but they do not have a legal professional exclusively to ensure their constitutional rights; However, in the cases of adults, according to Article 36 of the General Organic Code of Processes: Due to their state of defenselessness or economic, social or cultural status, they cannot hire private legal defense, for the protection of their rights, they have the power to resort to public defender's office and obtain a free legal and technical service. Therefore, it is necessary to reform this legal provision incorporating rules that allow in any judicial case of children and adolescents to be appointed a Public Defender specialized in children's rights. All this with the purpose of guaranteeing the norm of Article 13, of the Code of the Childhood and Adolescence that determines the progressive exercise of the rights and guarantees will be in favor of the children and adolescents according to their degree of development and maturity; prohibiting any restrictions on the exercise of these rights and guarantees. 5 Likewise, materials and methods were applied to develop the present investigation and also the interviews and surveys were carried out, which have helped me to propose a project of legal reform to the General Organic Code of Processes, to guarantee the progressive exercise of rights of the children and adolescents when they are immersed in judicial conflicts of parental authority, and require the legal technical defense of a Public Defender.